2019
DOI: 10.18805/lr-4077
|View full text |Cite
|
Sign up to set email alerts
|

Crop diversification of predominant Pearl millet based cropping system for higher productivity, resource-use efficiency and profitability in Semi-Arid Rajasthan

Abstract: Continuous adoption of Pearl millet-Wheat cropping system led to reduction in productivity which put a serious threat to its sustainability in semi-arid eastern plain zone of Rajasthan, India. Crop diversification with wider choice with a variety of crops is being promoted as an alternative to profit maximization with enhanced soil fertility status. Therefore, a long term experiment was initiated to evaluate the production potential, sustainability, resource-use efficiency and economics of nine Pearl millet ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Similar results were reported by Mall et al (2014) and Desai et al (2016). Sammauria et al (2020) reported that inclusion of vegetable crops such as onion and fenugreek in cropping systems fetched higher market prices, thus increasing net returns.…”
Section: System Profitabilitymentioning
confidence: 99%
“…Similar results were reported by Mall et al (2014) and Desai et al (2016). Sammauria et al (2020) reported that inclusion of vegetable crops such as onion and fenugreek in cropping systems fetched higher market prices, thus increasing net returns.…”
Section: System Profitabilitymentioning
confidence: 99%